COMIC NARRATIVE STRUCTURE: A TRIO OF HUMOUR TRADITIONS FROM PROSE TO SHORT FICTION - G. BANAZEER BANU,; Dr. S. GUNASEKARAN, (The Bioscan, 2025)
This research paper undertakes a comparative narratological study of comic narrative structures in the selected works of Mark Twain, Stephen Leacock, and R.K. Narayan, focusing on how their respective traditions—American tall tales, Canadian sketch-based comedies, and Indian short stories—employ distinct techniques of pacing, order, climax, and comic payoff. While humor is often viewed through linguistic or thematic lenses, this study explores how narrative form itself—its rhythm, construction, and genre conventions—generates comic effects. Twain’s episodic storytelling, built on oral traditions, relies on narrative detours and delayed punchlines; Leacock’s sketch-format narratives produce humor through static setups and exaggerated climaxes; and Narayan’s tightly woven short stories evoke gentle irony through linear development and subtle resolution. Using tools from narratology, structuralist theory, and genre analysis, this paper examines selected texts such as The Celebrated Jumping Frog, Sunshine Sketches of a Little Town, and Malgudi Days to identify how comic tension is built and released. The findings suggest that although the narrative mechanisms differ, all three writers share an underlying structure of subverted expectation, with humor emerging from rhythmic disruption and narrative incongruity. The study contributes to humor theory, comparative literature, and narrative studies by foregrounding how genre-specific narrative architecture influences reader response and the delivery of comic moments across cultures. Ultimately, it reveals that the form of storytelling—its movement, tempo, and resolution—is as crucial to humor as content or character.